Schistosomiasis - Husnawati, Eka; Lusiyana, Novyan (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2016)
Schistosomiasis, also known as bilharzia, is a zoonosis disease caused by blood flukes (trematodes) of the genus Schistosoma sp. There are a few species that can infect humans and animals, including Schistosoma aponicum, Schistosoma mansonia, Schistosoma hematobium, Schistosoma intercalatum Schistosoma guineensis and Schistosoma mekongi.1 This disease is endemic in 78 countries, in which 52 of them are countries with moderate-high level of endemicity. Schistosoma sp are very difficult to eliminate, because the transmission is highly influenced by evironmental, habitual, parasitic, vector, and host factors.